(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article examines the activities of the relevant state bodies, organizations and enterprises for the development and improvement of the system of providing the population and medical institutions of our country with cheap, high-quality medicines and medical products, coordination and control of the pharmaceutical activities of pharmacies. The article analyzes the reforms aimed at the further development of the pharmaceutical industry, improving the provision of the population with cheap and high-quality medicines and medical products as one of the priority areas for the development of the social sphere. In this article will be studied legal activity and responsibility of JSC "Dori-Darmon", the Agency for the Development of the Pharmaceutical Industry and the State Unitary Enterprise "O`zmedimpeks". Through these studies, the role of relevant government agencies, organizations and enterprises in the development and improvement of the system for providing the population with quality medicines and medical products in the country, coordination and control of pharmaceutical activities of pharmacies will be focused on specific tasks. Proposals will be developed to prevent duplication of powers, as well as to eliminate conditions for corruption in the procurement of medicines